Safety Evaluation of Natural Drugs in Chronic Skeletal Disorders: A Literature Review of Clinical Trials in the Past 20 years - Zhou, Dongyang; Zhang, Hao; Xue, Xu; Tao, Yali; Wang, Sicheng; Ren, Xiaoxiang; Su, Jiacan (Frontiers in Pharmacology, 2022)
Chronic skeletal disorders (CSDs), including degenerative diseases such as osteoporosis (OP) and autoimmune disorders, have become a leading cause of disability in an ageing society, with natural drugs being indispensable therapeutic options. The clinical safety evaluation (CSE) of natural drugs in CSDs has been given priority and has been intensively studied. To provide fundamental evidence for the clinical application of natural drugs in the elderly population, clinical studies of natural drugs in CSDs included in this review were selected from CNKI, Web of Science, PubMed, Science Direct and Google Scholar since 2001. Seventeen randomized controlled trials (RCTs) met our inclusion criteria: 4 articles were on OP, 7 on osteoarthritis（OA）, 4 on rheumatoid arthritis (RA) and 2 on gout. Common natural drugs used for the treatment of OP include Epimedium brevicornu Maxim. [Berberidaceae], Dipsacus asper Wall ex DC. [Caprifoliaceae] root, and Phalaenopsis cornu-cervi (Breda) Blume & Rchb.f.[ Orchidaceae], which have been linked to several mild adverse reactions, such as skin rash, gastric dysfunction, abnormal urine, constipation and irritability. The safety of Hedera helix L. [Araliaceae] extract, Boswellia serrata Roxb. [Burseraceae] extract and extract from perna canaliculus was evaluated in OA and upper abdominal pain, and unstable movements were obsrerved as major side effects. Adverse events, including pneumonia, vomiting, diarrhoea and upper respiratory tract infection, were reported when RA was treated with Tripterygium wilfordii, Hook. F. [Celastraceae][TwHF] polyglycosides and quercetin (Capsella bursa-pastoris (L.) Medik. [Brassicaceae]). The present review aimed to summarize the CSE results of natural drugs in CSDs and could provide evidence-based information for clinicians.